2013
DOI: 10.1152/ajpheart.00478.2012
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac function and lipid distribution in rats fed a high-fat diet: in vivo magnetic resonance imaging and spectroscopy

Abstract: Nagarajan V, Gopalan V, Kaneko M, Angeli V, Gluckman P, Richards AM, Kuchel PW, Sendhil Velan S. Cardiac function and lipid distribution in rats fed a high-fat diet: in vivo magnetic resonance imaging and spectroscopy. Am J Physiol Heart Circ Physiol 304: H1495-H1504, 2013. First published March 29, 2013 doi:10.1152/ajpheart.00478.2012.-Obesity is a major risk factor in the development of cardiovascular disease, type 2 diabetes, and its pathophysiological precondition insulin resistance. Very little is known … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 50 publications
2
11
0
Order By: Relevance
“…Recently, it was shown that carnitine supplementation can be used to restore myocardial free carnitine levels, followed by normalization of total fatty acid content in LCAD knockout mice (208). In rats exposed to a high-fat diet, cardiac lipid accumulation has been shown, together with moderate diabetes and mild cardiac hypertrophy (109). The cardiac lipid accumulation may be an early indication of the cardiovascular pathophysiology associated with type 2 diabetes.…”
Section: Tgs: Results From Animal Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it was shown that carnitine supplementation can be used to restore myocardial free carnitine levels, followed by normalization of total fatty acid content in LCAD knockout mice (208). In rats exposed to a high-fat diet, cardiac lipid accumulation has been shown, together with moderate diabetes and mild cardiac hypertrophy (109). The cardiac lipid accumulation may be an early indication of the cardiovascular pathophysiology associated with type 2 diabetes.…”
Section: Tgs: Results From Animal Studiesmentioning
confidence: 99%
“…In rats exposed to a high‐fat diet, cardiac lipid accumulation has been shown, together with moderate diabetes and mild cardiac hypertrophy . The cardiac lipid accumulation may be an early indication of the cardiovascular pathophysiology associated with type 2 diabetes.…”
Section: Spectroscopy Of Cardiac Metabolismmentioning
confidence: 99%
“…Cardiac steatosis is also regarded a potential mechanism for dysfunction in obesity and diabetes [28]. Recent MRI and spectroscopic analysis of rats fed a high-fat diet indicated that an accumulation of lipid in the myocardium was associated with impaired cardiac function [29]. Indeed, derangements in lipid metabolism due to accumulation of myocardial triacylglycerol can impair cardiac function and performance [28, 3034].…”
Section: Discussionmentioning
confidence: 99%
“…Further studies are needed to understand these complex interactions between cardiac steatosis and all these factors. Finally, although intramyocellular and extramyocellular lipids can be distinguished in skeletal muscle and animal hearts, [35][36][37] at present we cannot reliably differentiate these 2 lipid pools in human myocardium using our methods, and therefore we measure total lipid levels. Further work is needed to develop tools that can reliably differentiate the intramyocellular lipids (IMCL) and extramyocellular lipids (EMCL) in the human heart, but at the moment this is technical research and not ready for clinical studies.…”
Section: Study Limitationsmentioning
confidence: 93%